A Noise-Canceling TIA Topology Compatible With Large-Area Photodetectors in 40 nm CMOS Process - Gungordu, Ali Dogus; Yelten, Mustafa Berke (IEEE, 2022)
This paper presents a noise-canceling transimpedance amplifier (TIA) for plastic optical fiber (POF) and visible light communication (VLC), where large area photodetectors are common. The proposed TIA is based on the active shunt-shunt feedback topology for fast operation, and the structure is modified to improve the transimpedance (TI) gain and noise performance. The circuit is designed to meet the specifications of 1 Gbps-4 PAM optical communication over plastic fiber using a commercial 40 nm CMOS technology with a 1 V power supply. Post-layout simulations of the proposed noise-canceling TIA reveal that a bandwidth of 300 MHz and a TI gain of around 60 dBO have been acquired. These outcomes were achieved by considering a parasitic detector capacitance of 30 pF, where the integrated noise is reduced by about 20%.